Pentingnya Pendidikan Iman Berdasarkan Ensiklik Lumen Fidei - Stepanus Christian Danny Prasetyo; Maria Vianny Puspita; Carolus Borromeus Mulyatno (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Faith education, as outlined in this encyclical, emphasizes the instillation of integral spiritual, moral, and ethical values, which are not only cognitive but also affective and conative. Faith education, in this document, is seen as a shared responsibility, both within the family, school, and church community. This study uses a literature study method. There are several points that will be discussed in this study; Challenges of faith faced by young people today? What is the role of the Family, Church and Community in developing the faith of young people? and this study identifies the main principles of Lumen Fidei that can be applied in faith education, including the importance of dialogue between faith and reason in faith formation. The results of this study will discuss the relevance of faith education based on Lumen Fidei in the context of moral and character formation, the importance of integration between faith and reason, and the responsibility of the community in educating a generation of believers to develop the faith of young people to be a blessing to others.AbstrakPendidikan iman, sebagaimana diuraikan dalam ensiklik ini, menekankan pada penanaman nilai-nilai spiritual, moral, dan etika yang integral, yang bukan hanya bersifat kognitif tetapi juga afektif dan konatif. Pendidikan iman, dalam dokumen ini, dilihat sebagai tanggung jawab bersama, baik dalam lingkup keluarga, sekolah, maupun komunitas gereja. Penelitian ini menggunakan metode studi pustaka. Terdapat beberapa poin yang akan dibahas dalam penelitian ini, antara lain; Tantangan iman yang dihadapi saat ini oleh orang muda? Apa peran Keluarga, Gereja dan Komunitas dalam pengembangan iman orang muda? dan penelitian ini mengidentifikasi prinsip-prinsip utama dari Lumen Fidei yang dapat diterapkan dalam pendidikan iman, termasuk pentingnya dialog antara iman dan akal dalam pembinaan iman. Hasil dari penelitian ini akan membahas relevansi pendidikan iman berdasarkan Lumen Fidei dalam konteks pembentukan moral dan karakter, pentingnya integrasi antara iman dan akal, serta tanggung jawab komunitas dalam mendidik generasi beriman una mengembangkan iman orang muda menjadi berkat bagi sesama.